PENGEMBANGAN LKPD FISIKA BERBASIS CONTEXTUAL TEACHING AND LEARNING PADA MATERI FLUIDA DINAMIS UNTUK KELAS XI SMA - Revi Nur Ramadhanti; Zulhelmi Zulhelmi; Syahril Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: A physics student worksheets based on CTL is an worksheet that is compiled and designed with emphasis on the interrelationship between subject matter and the real world of student’s life. The purpose of this study was to develop a valid physical LKPD based on CTL on dynamic fluid material for class XI in high school. In this study, the validation stage was carried out by 3 lecturers of Physics Education who were experienced and also conducted trials limited to 22 students of class XI at SMAN 1 Gunung Toar. The research instrument was in the form of a questionnaire shaped a checklist. Data analysis in this study used descriptive analysis by calculating the index of each indicator used to determine the validity of the develop LKPD. The results of this study provide information that the developed of physical LKPD based on CTL in dynamic fluid material is valid and practical in the high and very high categories and can be used in learning to support the teaching and learning process so that it becomes better.Key Words: LKPD, Contextual Teaching and Learning, Dynamic Fluid, Descriptive Analysis.